Can a teacher-reported indicator be used for population monitoring of oral language skills at school entry? - Gray, Sarah; Kvalsvig, Amanda; O'Connor, Meredith; O'Connor, Elodie; Incledon, Emily; Tarasuik, Joanne; Goldfeld, Sharon (My University, 2018)
Purpose: Monitoring oral language skills at the population level would provide valuable data to inform policy decisions to better support children’s oral language skills in schools. The Australian Early Development Census (AEDC) is a teacher-rated population measure of early child development that includes a rating of children’s oral communication in the classroom (OCC). Method: This study evaluates the validity of the OCC indicator for population monitoring of children’s oral language skills,capitalising on data from two datasets: the 2012 AEDC cohort (n=289 973) and a subsample of children from the Longitudinal Study of Australian Children for whom AEDC data were also collected (n=720). Result: Construct validity was demonstrated by showing significant differences in OCC ratings between subpopulations of children who would be expected to differ in terms of oral language skills at school entry (e.g. children with a diagnosed speech-language impairment compared to those with no impairment). OCC ratings were associated with externally validated measures of language, suggesting convergent validity. No relationship was found between OCC ratings and physical health scores, indicating divergent validity. Conclusion: The findings support the use and interpretation of the OCC indicator as a tool for population-level monitoring of oral language in Australian school entrants.
International Journal of Speech-Language Pathology
Keywords: Child Development -- Speech and Language; Childhood and child development; Child Development; Speech and Language; Childhood and child development